MENINGKATKAN AKTIVITAS, KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR MATEMATIKA MENGGUNAKAN MODEL PANTING DI SEKOLAH DASAR - BAHARAS, VITA RIA SAFITRI; JANNAH, FATHUL; AGUSTA, AKHMAD RIANDY; HIDAYAT, ARI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2024)
This study aims to describe educator activities, analyze the improvement of activities, critical thinking skills, and learning outcomes of students. This research is a Class Action Research (PTK) which is carried out with 4 meetings. The subjects of this study are students of class VB SDN Telawang 3 Banjarmasin, with a total of 21 students in the second semester of the 2023/2024 school year. The types of data used in this study are qualitative and quantitative. Qualitative data was obtained through observation of educator activities, student activities and students' critical thinking skills, then using quantitative data for student learning outcomes obtained through written tests in groups and individuals. The analysis in this study uses descriptive analysis techniques and is described with tables, graphs and interpretations with percentages. The results of this study show that educator activity increased from a score of 23 to 31 with the